Review on the effect of palm oil fuel ash (POFA) on concrete - Eddy Syaizul Rizam Abdullah; Abdul Karim Mirasa; Hidayati Asrah (IWNEST Publisher, 2015)
Previous studies show that the addition of admixtures to the concrete or mortar has given a positive result which lead to the increasing of engineering properties especially in strength. The different sizes of admixture added to the concrete also give another positive result. The more fines of the admixture sizes, more benefits the concrete will have. This paper review on the Palm Oil Fuel Ash (POFA) as a new pozzolan in the construction industry. The fineness of the admixture was compared to the fineness of the cement. Different past researcher use different method for the grinding process to get the admixture size which finer than cement size particles. Previous study done by the past researcher revealed that the higher fineness of the POFA has given a good result to the strength. It can be concluded that the fineness of POFA give good effects to the properties of the concrete or mortar.